Exploring the Future of the Sports Industry Through an Economic Lens in 2031 - Rahmani, Nasrin; Naderi Nasab, Mahdi; Taheri, Morteza; Biniaz, Seyyed Abbas (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The purpose of the current research was to explore the future of the sports industry through an economic lens in 2031.Methodology: This study was applied in purpose and survey in method. The population of this research consisted of all experts in the sports industry, from whom 16 experts were sampled using purposive and snowball sampling methods. To collect data, semi-structured and in-depth interviews were employed. Initially, the researcher reviewed literature and theoretical foundations related to the sports industry. Then, semi-structured interviews were conducted with experts to identify influencing factors (16 interviews were conducted until data saturation was achieved). For analyzing mutual effects, a matrix questionnaire constructed by the researcher based on qualitative findings was used. For data processing, the Delphi technique was utilized in the first part of the study, and in the second part, the analysis of mutual effects was conducted using the Micmac software.Findings: Variables such as government financial sustainability, political stability, and human resource development were identified as influencing variables. Economic diplomacy, technology growth, management strategies, sports commerce, economic structural reform, investment networking, and exports were recognized as influenced variables. Economic security was seen as a dual-aspect variable and finally, variables such as hosting international events, legal and regulatory factors, economic infrastructure, competitiveness, media growth, and social networking were identified as independent variables.Conclusion: In this context, actions such as the development of economic sectors capable of creating jobs and promoting entrepreneurship, pricing of sports industry products, formulation of production indices, commitment to a resistance economy, listing sports clubs on the stock exchange, and combating economic corruption in sports must be prioritized by managers to assist the economy of the sports industry.